Evaluation of Complications After Open Reduction and Internal Fixation of Mandibular Condylar Base and Neck Fractures Using Trapezoidal Plates. Issue 5 (July 2020) - Smolka, Wenko; Liokatis, Paris; Cornelius, Carl-Peter
Abstract : Abstract: The purpose of the study was to evaluate the different fracture pattern of patients being treated with trapezoidal plate fixation of condylar base and neck fractures using the AOCMF Classification System to determine specific fracture pattern that are associated with failure of trapezoidal plate fixation. Ten patients with mandibular condylar base and neck fractures underwent internal fixation using trapezoidal plates. Fractures of the condylar process were classified according to the AOCMF Classification System using computed tomography data. The fracture pattern was compared to complications according to hardware failure such as plate or screw loosening and plate fracture. Plate and screw loosening of trapezoidal plates for fixation of condylar base and neck fractures was associated with fracture location in the neck region and major fragment displacement with contact loss between the proximal and distal fragment of the fracture. Further investigations such as finite-element analysis of different plating systems for fixation of condylar neck fractures are necessary to establish the optimal fixation technique for condylar neck fractures. Abstract : Supplemental Digital Content is available in the text